A New method for İnextensible Flows of Timelike Curves in 4-Dimensional LP-Sasakian Manifolds - Körpınar, Talat (World Scientific Publishing Co. Pte Ltd, 2015)
Inextensible flows of timelike curves plays an important role in practical applications. In this paper, we construct a new method for inextensible flows of timelike curves in a conformally flat, quasi conformally flat and conformally symmetric 4-dimensional LP-Sasakian manifold. With this new representation, we derive the necessary and sufficient condition for the given curve to be the inextensible flow. By using curvature tensor field, we give some characterizations for curvatures of a timelike curve in a conformally flat, quasi conformally flat and conformally symmetric 4-dimensional LP-Sasakian manifold. Finally, we obtain flows of some associated curves of timelike curves. © 2015 World Scientific Publishing Company.
Keywords: Fluid flow; Lorentzian almost paracontact manifolds; partial differential equation